2018
DOI: 10.1159/000495424
|View full text |Cite
|
Sign up to set email alerts
|

Palliative Care in Patients with Hematological Malignancies

Abstract: Patients with hematologic malignancies (HM) nowadays rarely receive palliative or hospice care, and studies on potential effects of integrated palliative care are rare. This narrative review provides a comprehensive overview on their current end-of-life care, first data on integrated specialist palliative care (SPC) and potential barriers. Symptom burden and distress in patients with HM seem to be comparable to other cancer patients, but their performance status and specific symptoms are even worse. Prolongati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
1
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 40 publications
0
16
1
1
Order By: Relevance
“…It has been suggested that an understanding of the unique trajectories of people with haematological cancers is needed by specialist palliative care teams [ 41 ] and also that early, integrated palliative care alongside haematology treatments can be beneficial, with improved physical and psychological symptom control amongst other benefits [ 42 ]. A collaborative approach, both within multidisciplinary haematology teams, but also between haematology and specialist palliative care teams, has been proposed [ 43 ]. Our data support the ongoing need for inpatient specialist palliative care services in both acute and elective oncology settings with such a high proportion of cancer patients spending significant amounts of time in hospital in the last year and months of life.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that an understanding of the unique trajectories of people with haematological cancers is needed by specialist palliative care teams [ 41 ] and also that early, integrated palliative care alongside haematology treatments can be beneficial, with improved physical and psychological symptom control amongst other benefits [ 42 ]. A collaborative approach, both within multidisciplinary haematology teams, but also between haematology and specialist palliative care teams, has been proposed [ 43 ]. Our data support the ongoing need for inpatient specialist palliative care services in both acute and elective oncology settings with such a high proportion of cancer patients spending significant amounts of time in hospital in the last year and months of life.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that the symptom burden is equal or greater in these patients than in those with solid malignancies. 22 -25 This, together with the adverse effects of chemotherapy, makes it more difficult to manage symptoms and predisposes patients to more visits to the emergency department and more hospitalizations, 26 which underscores that the care needs for patients with hematologic malignancies can differ substantially from those of patients with solid malignancies.…”
Section: Discussionmentioning
confidence: 99%
“…The integration of H1 into a network focusing on haematology and oncology is definitely an important factor. The conditions in H2 are more likely to reflect the reality in general care, especially because patients with a malignant haematological disease are under-represented in palliative care [34,35] and the integration of a hospice into a haematological/oncological network is no standard in Germany.…”
Section: Discussionmentioning
confidence: 99%